Evaluation of Mechanical Properties of FSW Al 2014 T4 & Al 6061 T6 Alloys - Kumar, Manoj; Sapra, Pawan Kumar; Sidhu, Balwinder Singh (Asian Review of Mechanical Engineering, 2013)
Friction Stir Welding (FSW) is fairly a recent technique that uses a non-consumable rotating welding tool to generate frictional heat and plastic deformation at the welding location while the material is in solid state. The principal advantages are low distortion, absence of melt related defects and high joint strength. Tool design and material plays a vital role in addition to the important parameters like tool rotational speed, welding speed and axial force. Friction Stir Welding (FSW) is a solid state welding process to join materials by generating frictional heat between a rotating tool and materials being welded. It was invented at The Welding Institute (TWI), Cambridge (U.K.) in 1991. Since then FSW has become a major joining process in the aerospace, railway and ship building industries especially in the fabrication of aluminium alloys. It is difficult to weld the aluminium alloys, using arc welding, gas welding and other welding processes. Friction Stir Welding on the other hand, can be used to join most Al alloys and better surface finish is achieved. Although the work piece does heat up during friction stir weld, the temperature does not reach the melting point. In this research work, rotational speed and traversing speed was considered for friction stir welding butt joint of Al alloy 2014 T4 & 6061 T6 alloys and further mechanical properties such as tensile strength, Vickers hardness and micro structure was studied.